2019
DOI: 10.1097/bot.0000000000001480
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Use in Open Reduction and Internal Fixation of Fractures of the Pelvis, Acetabulum, and Proximal Femur: A Randomized Controlled Trial

Abstract: Objective: To assess the safety and efficacy of tranexamic acid (TXA) use in fractures of the pelvic ring, acetabulum, and proximal femur. Design: Prospective, randomized controlled trial. Setting: Single Level 1 trauma center. Patients: Forty-seven patients were randomized to the study group, and 46 patients comprised the control group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…As with the data presented previously, several routes of administration were utilized with some studies included combination therapies (e.g., IV and topical TXA) [64,65]. Interestingly, while these metaanalyses found TXA to be effective in lowering transfusion rates and blood loss in lower energy trauma, a recent prospective trial by Spitler et al found minimal effect of TXA in higher energy trauma including pelvic, acetabular, and femur fractures in younger patients [66].…”
Section: Tranexamic Acidmentioning
confidence: 96%
“…As with the data presented previously, several routes of administration were utilized with some studies included combination therapies (e.g., IV and topical TXA) [64,65]. Interestingly, while these metaanalyses found TXA to be effective in lowering transfusion rates and blood loss in lower energy trauma, a recent prospective trial by Spitler et al found minimal effect of TXA in higher energy trauma including pelvic, acetabular, and femur fractures in younger patients [66].…”
Section: Tranexamic Acidmentioning
confidence: 96%
“…Two RCTs exploring the effects of intravenous TXA in PAF patients found that TXA offered no significant reduction in transfusion incidence, though one noted a reduction of total blood loss [70,71]. Both also concluded no significant increase in VTE with TXA use [70,71].…”
Section: Txa Usementioning
confidence: 99%
“…It is an effective agent against plasmin, tissue plasminogen activators, and plasminogen [9]. Several studies have reported that TXA can effectively reduce the rate of perioperative blood transfusion, blood loss, and drainage volume without increasing the risk of deep vein thrombosis (DVT) formation in trauma orthopedics [10][11][12][13][14]. In addition, it has been shown to be cost-effective.…”
Section: Introductionmentioning
confidence: 99%